Awareness and User Satisfaction With Archival Services At the Archives Management Department (RAMD) in Tanzania (Tanzania Journal for Population studies and Development, 2023)
This study assesses the awareness of, and user satisfaction with, archival services that the Records and Archives Management Department (RAMD) provides in Tanzania. It also identifies constraints undermining effective service access. Employing a descriptive research design and a mixed-methods approach, the study collected data from 81 respondents. Of these, four (4) were key informants who participated in interviews, with the remaining 77 taking part in a questionnaire survey. We subjected qualitative data to content analysis and processed quantitative data with the help of the SPSS. Then, Chi-square tests determined the association between the respondents’ awareness of archival services and their demographic characteristics. The study found moderate awareness among the respondents, with gender and education levels varyingly influencing such awareness. On the one hand, the majority of the respondents reported dissatisfaction with RAMD services, particularly the reading room space, service processes, and finding aids. On the other hand, a one-sample test revealed that the respondents were satisfied with record content and customer care. Inadequate ICT infrastructure, reading facilities, material deterioration, and the lack of web-based finding aids emerged as major constraints that contributed to user dissatisfaction. The study results suggest that RAMD should transition to the use of digital platforms (such as websites), as well as use of mass media (like radio and television), to enhance public awareness of RAMD’s services. Moreover, the RAMD should also create a more user-friendly environment, expand the reading room space, train employees, and digitise all the archival materials.